Phase Change Characteristics of Ultra-Thin Liquid Argon Film over different Flat Substrates at High Wall Superheat for Hydrophilic/Hydrophobic Wetting Condition: A Non-Equilibrium Molecular Dynamics Study - Hasan, Mohammad Nasim; Shavik, SM; Rabbi, KF; Mukut, KM; Morshed, AKMM (Journal of Chemical Engineering, 2017)
Non-equilibrium molecular dynamics simulations have been conducted to understand the effect of solid-liquid interfacial wettability and surface material on the phase change phenomena of the thin liquid argon film placed over flat substrate at high wall superheat. The molecular system consists of a three phase simulation domain involving solid wall, liquid argon and argon vapor. After the system is thermally equilibrated at 90K and kept in equilibrium for a while, a high wall superheat (250K that is far above the critical temperature of argon) is induced at the liquid boundary so that the liquid undergoes ultrafast heating. Both hydrophilic and hydrophobic surfaces were considered in the present study in order to observe the effect of surface wettability on phase change characteristics for three different solid substrate materials namely, Platinum (Pt), Silver (Ag) and Aluminium (Al). Results obtained in the present study are discussed in terms of transient atomic distribution inside system domain, heat flux characteristics across the solid-liquid interface together with evaporative mass flux from liquid argon. Simulation results show that, depending on the surface wetting condition, the phase change process appears to be very different (explosive/ diffusive) for all three substrate materials under consideration. Among three materials considered herein, Al is found to offer the least favourable condition for phase change process while Pt and Ag show similar heat and mass transfer characteristics for both hydrophilic and hydrophobic wetting conditions. Surface wettability effect is found to be more prominent than the effect of substrate material in thin film liquid phase change phenomena. Journal of Chemical Engineering, Vol. 29, No. 1, 2017: 49-55